2019
DOI: 10.3390/biom9110713
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms Underlying PTEN Loss in Human Tumors Suggest Potential Therapeutic Opportunities

Abstract: In this review, we will first briefly describe the diverse molecular mechanisms associated with PTEN loss of function in cancer. We will then proceed to discuss the molecular mechanisms linking PTEN loss to PI3K activation and demonstrate how these mechanisms suggest possible therapeutic approaches for patients with PTEN-null tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 187 publications
(218 reference statements)
0
17
0
1
Order By: Relevance
“…Overall, we would expect differences affecting hotspots or signatures to be minor, but in the absence of a rigorous analysis of sufficiently large datasets in the existing literature, it is not possible to make a definitive statement. In addition, PTEN expression is also subject to epigenetic controls 83 , which include promoter hypermethylation (particularly in MT-H tumors 84 ) and targeting by microRNAs 85 ; information bearing on the impact of these epigenetic control mechanisms is not available for the specimens analyzed here. However, based on the size of the dataset analyzed here, our study provides a detailed blueprint for segregating CRC tumors by PTEN mutation status within the landscape of various clinical subgroups and co-mutation patterns, providing context for subsequent analysis of epigenetic control of PTEN expression, and helping to enable rational design of future treatment combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we would expect differences affecting hotspots or signatures to be minor, but in the absence of a rigorous analysis of sufficiently large datasets in the existing literature, it is not possible to make a definitive statement. In addition, PTEN expression is also subject to epigenetic controls 83 , which include promoter hypermethylation (particularly in MT-H tumors 84 ) and targeting by microRNAs 85 ; information bearing on the impact of these epigenetic control mechanisms is not available for the specimens analyzed here. However, based on the size of the dataset analyzed here, our study provides a detailed blueprint for segregating CRC tumors by PTEN mutation status within the landscape of various clinical subgroups and co-mutation patterns, providing context for subsequent analysis of epigenetic control of PTEN expression, and helping to enable rational design of future treatment combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations or suppression of PTEN drives the development of diverse human cancers, including NSCLC [ 39 , 40 ]. PI3K signaling is one of the most crucial pathways in cancer biology, regulating cell cycle progression, survival, migration, invasion, and metabolism of cancer cells, and PTEN is the main negative regulator of it by dephosphorylating PIP 3 to PIP 2 [ 39 , 40 ]. PTEN also regulates chromosome stability, DNA repair, and apoptosis as a protein phosphatase [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K signaling is one of the most crucial pathways in cancer biology, regulating cell cycle progression, survival, migration, invasion, and metabolism of cancer cells, and PTEN is the main negative regulator of it by dephosphorylating PIP 3 to PIP 2 [ 39 , 40 ]. PTEN also regulates chromosome stability, DNA repair, and apoptosis as a protein phosphatase [ 39 , 40 ]. PTEN mutations are frequent in different cancer types; besides, PTEN expression is down-regulated at both transcriptional and post-transcriptional levels.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K phosphorylates and activates AKT, resulting in effects such as p21 stabilisation to aid survival [121] and MDM2 localisation to the nucleus to inhibit p53 [122]. The PI3K/AKT pathway is inhibited by PTEN (phosphatase and tensin homologue) [123][124][125], an important tumour suppressor [126]. Studies of acute lymphoblastic leukaemia (ALL) revealed that nutlin-3 upregulated p53 in all wild-type p53 cells, but apoptosis was induced only in PTEN-positive cells.…”
Section: Pi3k/akt Pten Mtor and Autophagymentioning
confidence: 99%